2008
DOI: 10.1016/j.fuproc.2007.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Production of activated carbons from coffee endocarp by CO2 and steam activation

Abstract: In this work the use of coffee endocarp as precursor for the production of activated carbons by steam and CO2 was studied. Activation by both methods produces activated carbons with small external areas and microporous structures having very similar mean pore widths. The activation produces mainly primary micropores and only a small volume of larger micropores. The CO2 activation leads to samples with higher BET surface areas and pore volumes when compared with samples produced by steam activation and with sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(70 citation statements)
references
References 24 publications
6
59
0
5
Order By: Relevance
“…The presence of flavonoids in extract of cocoa bean shell have been identified (Azizah et al, 1999) and in vitro research have demonstrated that flavonoids prevent low-density lipoprotein oxidation (Morel et al, 1996). Coffee silverskin is one of the main residues of coffee production and can cause serious environmental problems to soil (Nabais et al, 2008). Nevertheless, current investigations has proposed coffee silverskin as a good source of nutrient due to its antioxidant activity (Borrelli et al, 2004).…”
Section: Linear Programming Formulation Of a Dairy Drink Made Of Cocomentioning
confidence: 99%
“…The presence of flavonoids in extract of cocoa bean shell have been identified (Azizah et al, 1999) and in vitro research have demonstrated that flavonoids prevent low-density lipoprotein oxidation (Morel et al, 1996). Coffee silverskin is one of the main residues of coffee production and can cause serious environmental problems to soil (Nabais et al, 2008). Nevertheless, current investigations has proposed coffee silverskin as a good source of nutrient due to its antioxidant activity (Borrelli et al, 2004).…”
Section: Linear Programming Formulation Of a Dairy Drink Made Of Cocomentioning
confidence: 99%
“…The porosity of the char increases with the gasification extent. However, depending on the nature of the gas (CO 2 , H 2 O, O 2 or their mixture), the porosity as well as the pore size distribution do not evolve in a similar way [19][20][21][22][23]. Textural modifications during gasification impact directly on the internal gas diffusion process by the creation of small or large pores, widening others or opening closed ones.…”
Section: Gas Diffusion Inside the Charmentioning
confidence: 99%
“…In the specialized literature concerning the physical activation of carbonaceous materials by gasification with CO 2 or H 2 O, many authors found that the two gasses develop different porosities when reacting with the solid char [19][20][21][22][23]. For instance, Roman et al [21] found that during the gasification of olive stones with CO 2 , H 2 O or their mixtures, the volume of micropores and mesopores increased continuously.…”
Section: Introductionmentioning
confidence: 99%
“…Usually the temperature used for physical activation range between 700-1100 ºC for different lengths of time, ranging from few hours (Guo et al, 2009;Lin & Ritter, 2000;Nabais et al, 2008;Zhao et al, 2007) to 24 hours (Contreras et al, 2010). The activation time and temperature are very important variables since they can notably modify the microporosity of the resulting materials, and even the narrower mesoporosity.…”
Section: Activation: Physical or Chemical Activating Agent Activatinmentioning
confidence: 99%